2004
DOI: 10.1007/s00213-003-1567-y
|View full text |Cite
|
Sign up to set email alerts
|

Fluvoxamine dose-dependent interaction with haloperidol and the effects on negative symptoms in schizophrenia

Abstract: Augmentation with low-dose fluvoxamine (50-100 mg/day) to antipsychotic treatment may improve the negative symptoms in schizophrenic patients, but involves a risk of drug-drug interaction. We studied the effects of fluvoxamine on plasma concentrations of haloperidol and reduced haloperidol, and their clinical symptoms, in haloperidol treated patients. Twelve schizophrenic inpatients with prevailingly negative symptoms receiving haloperidol 6 mg/day were additionally treated with incremental doses of fluvoxamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, improvement in negative symptoms of schizophrenic patients treated with SSRI and haloperidol did not correlate with the increase of antipsychotic levels in plasma. 26,27 Increasing antipsychotic drug levels does not increase the overall efficacy or the range of responsive symptoms, and may have adverse effects. 28 -30 Antidepressant doses used in antidepressant-antipsychotic combinations are usually lower than those used in monotherapy.…”
Section: Selective Serotonin Reuptake Inhibitor-antipsychotic Therapymentioning
confidence: 99%
“…However, improvement in negative symptoms of schizophrenic patients treated with SSRI and haloperidol did not correlate with the increase of antipsychotic levels in plasma. 26,27 Increasing antipsychotic drug levels does not increase the overall efficacy or the range of responsive symptoms, and may have adverse effects. 28 -30 Antidepressant doses used in antidepressant-antipsychotic combinations are usually lower than those used in monotherapy.…”
Section: Selective Serotonin Reuptake Inhibitor-antipsychotic Therapymentioning
confidence: 99%
“…Recent studies reported that adding a selective serotonin reuptake inhibitor (SSRI) such as fluvoxamine Silver and Nassar, 1992 ;Silver and Shmugliakov, 1998 ;Yasui-Furukori et al, 2004) or fluoxetine (Goff and Evins, 1998) to typical antipsychotics can improve negative symptoms in patients who did not respond to antipsychotics alone. The improvement included key negative symptoms primary to the illness (Silver et al, 2003a) and could be detected as early as 2 wk after treatment onset (Silver et al, 2003c).…”
Section: Introductionmentioning
confidence: 99%
“…Dose-dependent inhibition of haloperidol metabolism has been described with 150 mg of fluvoxamine resulting in 160% increase in haloperidol levels. 6 It is unlikely that the NMS reaction was precipitated by the increased serum haloperidol level since the oral haloperidol had been discontinued 2 weeks prior to the reaction (elimination halflife 18 hours) and the haloperidol level had likely declined significantly after its discontinuation despite the interaction with fluvoxamine, although a subsequent level was not obtained. In addition, both haloperidol decanoate and fluvoxamine had been prescribed for several months at the same dose prior to the NMS reaction.…”
Section: Discussionmentioning
confidence: 99%